Աբխազիայի կարգավիճակի ձևավորումը խորհրդային պետականության պայմաններում (1921-1931 թթ.) - Մաիլյան, Բենիամին («Զանգակ - 97»)
The study of ihc condition of Abkhazia in soviel Male period have an importance in ihc coniexi of ihc modern relalionships beiween georgians and abkhazians. After sovictizalion of Georgia, befor ihc formation of ihc USSR, communisi leaders of Soviel Abkha/.ia seek for ihe sialus of indepcndence. whieh formally was given from central communisi bodics. Düring ihc formation the federalion of south Caucasis republies, Abkha/.ia was includcd Soviel Rcpublic of Georgia based on an alliance Agreement. Iliglicr staie and parly bodics of the USSR regarded Abkhazia as autonnmy region, bui it was called agrcemeni republic, such concessions were made, because the greal part ofahkhaz nationality didn'l want to be under the administrative patronage of Georgia. The status of agreement rcpublic of Abkhazia in 1922-1930 had the same formal character, as the independence in 1921. In 1931 Abkhazia was iransformed into an autonoiny republic in Georgia SSR as ihc USSR hadn't the analogy of agreement republic.
Keywords: Պատմություն; Քաղաքականություն